Preparation method and application of TMA-MXene / CoV-LDH / NF composite material

By growing TMA-MXene/CoV-LDH/NF composites in situ on nickel foam, the problems of poor conductivity and low energy density of supercapacitor electrode materials are solved, and electrochemical properties of high specific capacitance and high energy density are achieved.

CN117690732BActive Publication Date: 2025-03-28QIQIHAR UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311782756.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-22
Publication Date
2025-03-28
Estimated Expiration
2043-12-22

AI Technical Summary

Technical Problem

The energy density of existing supercapacitors is low, limiting their application range, and most electrode materials have poor conductivity, affecting electrochemical properties.

Method used

In situ growth method was used to prepare TMA-MXene/CoV-LDH/NF composites on foam nickel (NF), and the specific surface area was increased by vertical growth structure and electrochemical performance was improved.

Benefits of technology

Supercapacitor electrode materials with high specific capacitance provide higher energy density and better electrochemical properties, avoid the use of adhesives and improve the stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117690732B_ABST
    Figure CN117690732B_ABST
Patent Text Reader

Abstract

A preparation method and application of a TMA-MXene / CoV-LDH / NF composite material, which relates to a preparation method and application of a MXene-based material. The purpose of the present invention is to use NF as a substrate to prepare a nanocomposite material that can be used as a supercapacitor electrode and has a three-dimensional self-supporting structure prepared by an in-situ growth method, in order to prepare a V-based nanocomposite material in a supercapacitor electrode material. 2 CT x MXene-based composites offer the prospect of developing new self-supporting structural electrode materials. 2 CT x MXene; 2. Preparation of TMA‑V 2 CT x Colloidal solution; III. Preparation of TMA‑V 2 CT x / CoV‑LDH / NF; A TMA‑MXene / CoV‑LDH / NF composite material is used as a supercapacitor electrode material. The present invention can obtain a TMA‑MXene / CoV‑LDH / NF composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a preparation method and application of a MXene-based composite material. Background Art

[0002] Nowadays, the continuous depletion of fossil energy and climate change have made the search for renewable energy a top priority. As a solution to the energy crisis, energy storage devices are being vigorously developed. At present, the power storage market is mainly dominated by batteries, while capacitors are more suitable for small-scale and short-term applications (mainly electronic products). Rechargeable batteries and supercapacitors (SCs) have received widespread attention as the most promising energy storage devices. Recently, supercapacitors have been considered as alternatives to batteries due to their higher power density, better cycle performance, and faster charging and discharging speeds. Due to their low energy density, the development and application of capacitors are subject to some restrictions. The specific capacitance of electrode materials in energy storage batteries has a great influence on the energy density. Therefore, electrode materials with high specific capacitance are very important in supercapacitors.

[0003] Supercapacitors are candidates for electrochemical energy storage devices due to their long service life, safety, no leakage, and wear resistance. However, major problems such as poor energy density of most supercapacitors have largely hindered their application. In order to build energy storage devices with high energy density without compromising high power density, a lot of work has been invested in manufacturing new materials with high performance. Therefore, the rational design of targeted nano / microstructures is of great significance. Two-dimensional (2D) materials have been widely studied as important electrode materials. In particular, two-dimensional thin layer structures can more effectively improve the utilization of electrode active sites, and the prominent nanostructures can also accelerate the transmission speed of ions and electrons. As a new two-dimensional material, MXene has been widely used in SC. The uniqueness of MXene lies in its layered structure, excellent chemical and environmental stability, and excellent hydrophilicity. Overall, V2CT x It is a typical and promising material of MXene, V2CT x The electron storage capacity of the electrode in SC is better than that of carbon materials. x Inserting a large number of cations between layers and designing the structure of MXene-based materials are the key to improving V2CT. x It is necessary to have an effective method for V2CT x Exfoliation and delamination are performed to fully utilize its specific surface area.

[0004] Currently, based on TMA-V2CT xBased on the energy storage mechanism and its good specific surface area, nickel foam (NF) with a self-supporting structure is used as the current collector to design a more stable three-dimensional structural material, and a pseudocapacitive material with a relatively high specific capacity is selected to prepare a composite electrode. After the two materials with different energy storage mechanisms are combined, not only can rapid charge adsorption / desorption occur on the electrode surface, but also rapid redox reactions can occur, thereby providing high specific capacitance. It has been proven that the structure of the composite material plays a vital role in improving the performance of the material. The composite electrode prepared by the in situ growth synthesis method avoids the influence of the binder in the traditional electrode preparation process and can better disperse and support the electrode. Stable V2CT x It can inhibit the aggregation of metal hydroxide flake structures and increase the charge transfer rate, thereby improving the electrochemical performance. x and pseudocapacitive materials to prepare composite materials for use in the field of supercapacitors has not yet been achieved. Summary of the invention

[0005] The purpose of the present invention is to solve the above-mentioned technical problems and to provide a preparation method and application of a TMA-MXene / CoV-LDH / NF composite material.

[0006] The purpose of the present invention is to use NF as a substrate to prepare a three-dimensional self-supporting nanocomposite material that can be used as a supercapacitor electrode by an in-situ growth method, so as to prepare a V2CT-based nanocomposite material in a supercapacitor electrode material. x MXene-based composites offer the prospect of developing new self-supporting structural electrode materials.

[0007] A method for preparing a TMA-MXene / CoV-LDH / NF composite material is completed by the following steps:

[0008] 1. Preparation of V2CT x MXene:

[0009] ①, stir lithium fluoride and hydrochloric acid to obtain mixture Ⅰ;

[0010] ②, dissolve V2AlC in mixture Ⅰ, stir evenly to obtain mixture Ⅱ;

[0011] ③, transfer the mixture II to a polytetrafluoroethylene high-pressure reactor for hydrothermal reaction, and then cool naturally to room temperature to obtain the reaction product I;

[0012] ④. Use hydrochloric acid, deionized water and anhydrous ethanol to centrifuge and wash the reaction product I in sequence until the pH value of the supernatant is higher than 6. After removing the supernatant, the precipitate V2CT is obtained. x MXene;

[0013] 2. Preparation of TMA-V2CT x Colloidal solution:

[0014] ① Pour tetramethylammonium hydroxide solution into the precipitate V2CT x MXene was stirred at room temperature for 12 h to obtain mixed solution Ⅰ;

[0015] ②, centrifuge the mixed solution I with anhydrous ethanol and deionized water until pH = 7, add deionized water again and sonicate for 1 hour under a nitrogen atmosphere, centrifuge and collect the supernatant to obtain the reaction product II;

[0016] ③. Dissolve the reaction product II in a lithium chloride aqueous solution and let it stand to obtain a precipitate, which is the reaction product III;

[0017] ④. Wash the reaction product III with deionized water, add deionized water to the washed reaction product III and ultrasonicate for 30 minutes under nitrogen atmosphere to obtain TMA-V2CT x Colloidal solutions;

[0018] 3. Preparation of TMA-V2CT x / CoV-LDH / NF:

[0019] ① Dissolve cobalt chloride hexahydrate, vanadium chloride and urea in deionized water and stir evenly to obtain solution I;

[0020] ②, nickel foam and TMA-V2CT x The colloidal solution is transferred to solution I and stirred evenly to obtain mixture III;

[0021] ③, transfer the mixture III to a polytetrafluoroethylene autoclave for hydrothermal reaction, and then cool naturally to room temperature to obtain the reaction product IV;

[0022] ④. Use deionized water and anhydrous ethanol to wash the reaction product IV, and vacuum dry the washed reaction product IV to obtain TMA-V2CT x / CoV-LDH / NF, that is, TMA-MXene / CoV-LDH / NF composite material.

[0023] A TMA-MXene / CoV-LDH / NF composite material is used as a supercapacitor electrode material.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. TMA-V2CT prepared by the present invention x / CoV-LDH / NF composite materials can effectively improve the poor conductivity of LDH materials and the stacking of MXene nanosheets. The composite materials have a vertical growth structure, which can effectively increase the specific surface area of ​​the material and provide more active sites for pseudocapacitive reactions.

[0026] 2. TMA-V2CT prepared by the present invention x As a supercapacitor electrode material, the / CoV-LDH / NF composite material has a high specific capacitance of 2374.0F / g at 1A / g, and can be used in supercapacitors with high energy density;

[0027] 3. A TMA-V2CT prepared by the present invention x The overall structure of the / CoV-LDH / NF composite material contains a two-dimensional layered structure of MXene and a vertical three-dimensional structure constructed by nickel foam, which avoids the use of adhesives, is conducive to increasing active sites and improving the conductivity and stability of the material;

[0028] 4. A TMA-V2CT prepared in this embodiment x The method of preparing / CoV-LDH / NF composite material has the characteristics of simple process, green and environmentally friendly preparation process, easy operation and low equipment requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 TMA-V2CT prepared in Example 1 x SEM images of / CoV-LDH / NF;

[0030] Figure 2 TMA-V2CT prepared in Example 1 x Transmission electron microscopy image of / CoV-LDH / NF;

[0031] Figure 3 TMA-V2CT prepared in Examples 1 to 3 x / CoV-LDH / NF,TMA-V2CT x Comparison of cyclic voltammetry curves of / CoV-LDH and CoV-LDH / NF at the same scan rate;

[0032] Figure 4 TMA-V2CT prepared in Examples 1 to 3 x / CoV-LDH / NF,TMA-V2CT x Comparison of constant current charge and discharge of / CoV-LDH and CoV-LDH / NF at the same current density;

[0033] Figure 5 TMA-V2CT prepared in Examples 1 to 3x / CoV-LDH / NF,TMA-V2CT x Impedance comparison chart of / CoV-LDH and CoV-LDH / NF;

[0034] Figure 6 TMA-V2CT prepared in Example 1 x Constant current charge and discharge diagrams of / CoV-LDH / NF at different current densities. DETAILED DESCRIPTION

[0035] Specific implementation method 1: This implementation method is a method for preparing a TMA-MXene / CoV-LDH / NF composite material, which is specifically completed by the following steps:

[0036] 1. Preparation of V2CT x MXene:

[0037] ①, stir lithium fluoride and hydrochloric acid to obtain mixture Ⅰ;

[0038] ②, dissolve V2AlC in mixture Ⅰ, stir evenly to obtain mixture Ⅱ;

[0039] ③, transfer the mixture II to a polytetrafluoroethylene high-pressure reactor for hydrothermal reaction, and then cool naturally to room temperature to obtain the reaction product I;

[0040] ④. Use hydrochloric acid, deionized water and anhydrous ethanol to centrifuge and wash the reaction product I in sequence until the pH value of the supernatant is higher than 6. After removing the supernatant, the precipitate V2CT is obtained. x MXene;

[0041] 2. Preparation of TMA-V2CT x Colloidal solution:

[0042] ① Pour tetramethylammonium hydroxide solution into the precipitate V2CT x MXene was stirred at room temperature for 12 h to obtain mixed solution Ⅰ;

[0043] ②, centrifuge the mixed solution I with anhydrous ethanol and deionized water until pH = 7, add deionized water again and sonicate for 1 hour under a nitrogen atmosphere, centrifuge and collect the supernatant to obtain the reaction product II;

[0044] ③. Dissolve the reaction product II in a lithium chloride aqueous solution and let it stand to obtain a precipitate, which is the reaction product III;

[0045] ④. Wash the reaction product III with deionized water, add deionized water to the washed reaction product III and ultrasonicate for 30 minutes under nitrogen atmosphere to obtain TMA-V2CT xColloidal solutions;

[0046] 3. Preparation of TMA-V2CT x / CoV-LDH / NF:

[0047] ① Dissolve cobalt chloride hexahydrate, vanadium chloride and urea in deionized water and stir evenly to obtain solution I;

[0048] ②, nickel foam and TMA-V2CT x The colloidal solution is transferred to solution I and stirred evenly to obtain mixture III;

[0049] ③, transfer the mixture III to a polytetrafluoroethylene autoclave for hydrothermal reaction, and then cool naturally to room temperature to obtain the reaction product IV;

[0050] ④. Use deionized water and anhydrous ethanol to wash the reaction product IV, and vacuum dry the washed reaction product IV to obtain TMA-V2CT x / CoV-LDH / NF, that is, TMA-MXene / CoV-LDH / NF composite material.

[0051] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the mass ratio of lithium fluoride to hydrochloric acid in step 1① is (1.0 g to 2.0 g): 20 mL, and the concentration of hydrochloric acid is 12 mol / L. The other steps are the same as those in specific embodiment 1.

[0052] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the mass ratio of V2AlC to lithium fluoride in step 1② is 1:2. The other steps are the same as those in specific implementation method 1 or 2.

[0053] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the temperature of the hydrothermal reaction in step 1 ③ is 90° C. and the time of the hydrothermal reaction is 72 hours. The other steps are the same as those of specific embodiments 1 to 3.

[0054] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the volume ratio of tetramethylammonium hydroxide to deionized water in the tetramethylammonium hydroxide solution in step 2① is 1:5. The other steps are the same as those in specific embodiments 1 to 4.

[0055] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: the precipitate V2CT described in step 2① x The mass ratio of MXene to the volume ratio of tetramethylammonium hydroxide solution is 0.5 g: 20 mL. The other steps are the same as those in the first to fifth embodiments.

[0056] Specific embodiment 7: The difference between this embodiment and specific embodiments 1 to 6 is that the mass ratio of lithium chloride to deionized water in the lithium chloride aqueous solution described in step 2 ③ is 1:10; the standing time described in step 2 ③ is 24h; the TMA-V2CT described in step 2 ④ x The mass fraction of the colloidal solution is 0.1%. The other steps are the same as those of the first to sixth embodiments.

[0057] Specific embodiment 8: The difference between this embodiment and specific embodiments 1 to 7 is that the molar ratio of cobalt chloride hexahydrate, vanadium chloride and urea in step 3① is 15:12:10; the volume ratio of the amount of cobalt chloride hexahydrate in step 3① to deionized water is 0.6 mol:20 mL; the TMA-V2CT in step 3② is x The volume ratio of the colloidal solution to solution I is 1:2. The other steps are the same as those of the specific embodiments 1 to 7.

[0058] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the temperature of the hydrothermal reaction in step 3 ③ is 120°C, and the time of the hydrothermal reaction is 12h; the temperature of the vacuum drying in step 3 ④ is 60°C to 80°C, and the time of the vacuum drying is 10h to 12h. The other steps are the same as those in specific embodiments 1 to 8.

[0059] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that a TMA-MXene / CoV-LDH / NF composite material is used as a supercapacitor electrode material. The other steps are the same as those of specific embodiments 1 to 9.

[0060] The following examples are used to verify the beneficial effects of the present invention:

[0061] Example 1: A TMA-V2CT x The preparation method of the / CoV-LDH / NF composite material is specifically completed by the following steps:

[0062] 1. Preparation of V2CT x :

[0063] ①, stir 2.0g lithium fluoride and 20mL 12mol / L hydrochloric acid to obtain mixture Ⅰ;

[0064] ②, dissolve 1.0g of V2AlC powder in mixture I in batches within 6 minutes, stir for 10 minutes until uniform, and obtain mixture II;

[0065] ③. Transfer the mixture II to a polytetrafluoroethylene high-pressure reactor for hydrothermal reaction at a temperature of 90°C for 72 hours, and then cool naturally to room temperature to obtain reaction product I;

[0066] ④. Use 60 mL of 2 mol / L hydrochloric acid, deionized water and anhydrous ethanol to centrifuge and wash the reaction product I in sequence until the pH value of the supernatant is higher than 6. After removing the supernatant, the precipitate V2CT is obtained. x ;

[0067] 2. Preparation of TMA-V2CT x Colloidal solution:

[0068] ① Pour tetramethylammonium hydroxide solution into the precipitate V2CT x Mxene, stirred at room temperature for 12 h to obtain a mixed solution Ⅰ;

[0069] The volume ratio of tetramethylammonium hydroxide to deionized water in the tetramethylammonium hydroxide solution described in step 2① is 1:5;

[0070] The precipitate V2CT described in step 2① x The mass ratio of Mxene to the volume of tetramethylammonium hydroxide solution is 0.5 g:20 mL;

[0071] ②, centrifuge the mixed solution I with anhydrous ethanol and deionized water until pH = 7, add deionized water again and sonicate for 1 hour under a nitrogen atmosphere, centrifuge and collect the supernatant to obtain the reaction product II;

[0072] ③. Dissolve the reaction product II in a lithium chloride aqueous solution and let it stand for 24 hours to obtain a precipitate, which is the reaction product III;

[0073] The mass ratio of lithium chloride to deionized water in the lithium chloride aqueous solution described in step 2③ is 1:10;

[0074] ④. Wash the reaction product III with deionized water, add deionized water to the washed reaction product III and ultrasonicate for 30 minutes under nitrogen atmosphere to obtain TMA-V2CT x Colloidal solutions;

[0075] TMA-V2CT as described in step 2④ x The mass fraction of the colloidal solution is 0.1%;

[0076] 3. Preparation of TMA-V2CT x / CoV-LDH / NF:

[0077] ① Dissolve 0.6 mol of cobalt chloride hexahydrate, 0.48 mol of vanadium chloride, and 0.4 mol of urea in 20 mL of deionized water, stir evenly, and obtain solution I;

[0078] ②, 1cm×4cm×0.1cm nickel foam and 10mL TMA-V2CT x The colloidal solution is transferred to the solution Ⅰ obtained in step 3①, and stirred evenly to obtain a mixture Ⅲ;

[0079] ③. Transfer the mixture III to a polytetrafluoroethylene autoclave for hydrothermal reaction at a temperature of 120°C for 12 hours, and then cool naturally to room temperature to obtain a reaction product IV.

[0080] ④. The reaction product IV was washed with deionized water and anhydrous ethanol, and the washed reaction product IV was vacuum dried at 60°C for 10 h to obtain TMA-V2CT x / CoV-LDH / NF, that is, TMA-MXene / CoV-LDH / NF composite material.

[0081] Example 2: The difference between this example and Example 1 is that 10 mL TMA-V2CT is not added in step 3② x The other steps and parameters are the same as those in Example 1.

[0082] The product obtained in Example 2 is CoV-LDH / NF.

[0083] Embodiment 3: The difference between this embodiment and embodiment 1 is that in step 3②, 1 cm×4 cm×0.1 cm nickel foam is not added. The other steps and parameters are the same as those in embodiment 1.

[0084] The product obtained in Example 3 is TMA-V2CT x / CoV-LDH.

[0085] This experiment uses a three-electrode system: the electrolyte solution is 3 mol / L potassium hydroxide solution, the counter electrode is a platinum electrode, the reference electrode is a mercury / mercuric oxide electrode, and the working electrodes are TMA-V2CT x / CoV-LDH / NF,TMA-V2CT x / CoV-LDH, CoV-LDH / NF.

[0086] Figure 1 TMA-V2CT prepared in Example 1 x SEM images of / CoV-LDH / NF;

[0087] like Figure 1 As shown, the prepared TMA-V2CTx The structure of / CoV-LDH / NF under scanning electron microscopy is that NF is the substrate, and CoV-LDH grows vertically on TMA-V2CT x On, and CoV-LDH and TMA-V2CT x A three-dimensional self-supporting structure uniformly grown on NF can effectively provide more reactive sites, increase the specific surface area, and improve the electrochemical activity and capacitance performance of the material.

[0088] Figure 2 TMA-V2CT prepared in Example 1 x Transmission electron microscopy image of / CoV-LDH / NF;

[0089] like Figure 2 TMA-V2CT prepared as shown x The / CoV-LDH / NF was vertically grown on TMA-V2CT under transmission electron microscopy. x The cross-links between the CoV-LDH nanosheets on the surface are very thin and do not aggregate together, further confirming the TMA-V2CT x Effectiveness in inhibiting CoV-LDH aggregation.

[0090] Figure 3 TMA-V2CT prepared in Examples 1 to 3 x / CoV-LDH / NF,TMA-V2CT x Comparison of cyclic voltammetry curves of / CoV-LDH and CoV-LDH / NF at the same scan rate;

[0091] like Figure 3 As shown, it is TMA-V2CT x / CoV-LDH / NF,TMA-V2CT x Cyclic voltammetry curves of / CoV-LDH and CoV-LDH / NF at the same scan rate, the voltage test range of cyclic voltammetry is 0-0.6V;

[0092] from Figure 3 It can be observed that compared with TMA-V2CT x / CoV-LDH and CoV-LDH / NF, TMA-V2CT x / CoV-LDH / NF has the largest redox current and closed area, indicating that TMA-V2CT x / CoV-LDH / NF has the best electrochemical performance.

[0093] Figure 4 TMA-V2CT prepared in Examples 1 to 3 x / CoV-LDH / NF,TMA-V2CT x Comparison of constant current charge and discharge of / CoV-LDH and CoV-LDH / NF at the same current density;

[0094] like Figure 4 As shown, it is TMA-V2CT x / CoV-LDH / NF,TMA-V2CT x The charge and discharge performance test curves of / CoV-LDH and CoV-LDH / NF at a current density of 1A / g. The voltage test window of constant current charge and discharge in this experiment is 0-0.5V;

[0095] from Figure 4 It can be seen that the potential of the three materials in the charge / discharge curves changes nonlinearly with the cycle time, showing typical pseudocapacitive behavior. x The / CoV-LDH / NF electrode showed a longer discharge time, indicating the best electrochemical performance and excellent energy storage capacity, which was consistent with the conclusion of the cyclic voltammetry curve.

[0096] Figure 5 TMA-V2CT prepared in Examples 1 to 3 x / CoV-LDH / NF,TMA-V2CT x Impedance comparison chart of / CoV-LDH and CoV-LDH / NF;

[0097] like Figure 5 As shown, it is TMA-V2CT x / CoV-LDH / NF,TMA-V2CT x / CoV-LDH, CoV-LDH / NF were subjected to electrochemical impedance spectroscopy in the frequency range of 0.01 Hz to 100 kHz;

[0098] from Figure 5 As can be seen: TMA-V2CT x The / CoV-LDH / NF electrode material has a relatively small internal resistance, fast ion and electron transfer, and exhibits good electrochemical performance.

[0099] Figure 6 TMA-V2CT prepared in Example 1 x Constant current charge and discharge diagram of / CoV-LDH / NF at different current densities;

[0100] like Figure 6 As shown, it is TMA-V2CT x Charge / discharge curves of / CoV-LDH / NF at different current densities;

[0101] from Figure 6 As can be seen: TMA-V2CT x The charge / discharge curves of / CoV-LDH / NF as electrode material when current densities were 1A / g, 2A / g, 3A / g, 5A / g, 8A / g, 10A / g and 20A / g respectively. The voltage test window of constant current charge / discharge in this experiment was 0-0.5V. When the current density was 1A / g, the specific capacitance was the largest, reaching 2374.0F / g. When the current density was 20A / g, the specific capacitance was 1628.0F / g, and the retention rate was 68.6%, showing good electrochemical performance.

[0102] In summary: TMA-V2CT prepared in Example 1 x The / CoV-LDH / NF composite material has high capacitor performance and excellent stability, and can be used as an active material for supercapacitors.

Claims

1. A method for preparing a TMA-MXene / CoV-LDH / NF composite material, characterized in that The preparation method is specifically completed according to the following steps:

1. Preparation of V2CT x MXene: ①, stir lithium fluoride and hydrochloric acid to obtain mixture Ⅰ; ②, dissolve V2AlC in mixture Ⅰ, stir evenly to obtain mixture Ⅱ; ③, transfer the mixture II to a polytetrafluoroethylene high-pressure reactor for hydrothermal reaction, and then cool naturally to room temperature to obtain the reaction product I; ④. Use hydrochloric acid, deionized water and anhydrous ethanol to centrifuge and wash the reaction product I in sequence until the pH value of the supernatant is higher than 6. After removing the supernatant, the precipitate V2CT is obtained. x MXene; 2. Preparation of TMA-V2CT x Colloidal solution: ① Pour tetramethylammonium hydroxide solution into the precipitate V2CT x MXene was stirred at room temperature for 12 h to obtain mixed solution Ⅰ; ②, centrifuge the mixed solution I with anhydrous ethanol and deionized water until pH = 7, add deionized water again and sonicate for 1 hour under a nitrogen atmosphere, centrifuge and collect the supernatant to obtain the reaction product II; ③. Dissolve the reaction product II in a lithium chloride aqueous solution and let it stand to obtain a precipitate, which is the reaction product III; ④. Wash the reaction product III with deionized water, add deionized water to the washed reaction product III and ultrasonicate for 30 minutes under nitrogen atmosphere to obtain TMA-V2CT x Colloidal solutions; 3. Preparation of TMA-V2CT x / CoV-LDH / NF: ① Dissolve cobalt chloride hexahydrate, vanadium chloride and urea in deionized water and stir evenly to obtain solution I; ②, nickel foam and TMA-V2CT x The colloidal solution is transferred to solution I and stirred evenly to obtain mixture III; ③, transfer the mixture III to a polytetrafluoroethylene autoclave for hydrothermal reaction, and then cool naturally to room temperature to obtain the reaction product IV; ④. Use deionized water and anhydrous ethanol to wash the reaction product IV, and vacuum dry the washed reaction product IV to obtain TMA-V2CT x / CoV-LDH / NF, that is, TMA-MXene / CoV-LDH / NF composite material.

2. The method for preparing a TMA-MXene / CoV-LDH / NF composite material according to claim 1, characterized in that The mass ratio of lithium fluoride described in step 1① to the volume ratio of hydrochloric acid is (1.0g~2.0g):20mL, and the concentration of hydrochloric acid is 12mol / L.

3. The method for preparing a TMA-MXene / CoV-LDH / NF composite material according to claim 1, characterized in that The mass ratio of V2AlC and lithium fluoride described in step 1② is 1:

2.

4. The method for preparing a TMA-MXene / CoV-LDH / NF composite material according to claim 1, characterized in that The temperature of the hydrothermal reaction described in step 1③ is 90°C, and the time of the hydrothermal reaction is 72h.

5. The method for preparing a TMA-MXene / CoV-LDH / NF composite material according to claim 1, characterized in that In step 2①, the volume ratio of tetramethylammonium hydroxide to deionized water in the tetramethylammonium hydroxide solution is 1:

5.

6. The method for preparing a TMA-MXene / CoV-LDH / NF composite material according to claim 1, characterized in that The precipitate V2CT described in step 2① x The mass ratio of MXene to the volume of tetramethylammonium hydroxide solution was 0.5 g:20 mL.

7. The method for preparing a TMA-MXene / CoV-LDH / NF composite material according to claim 1, characterized in that The mass ratio of lithium chloride to deionized water in the lithium chloride aqueous solution in step 2③ is 1:10; the standing time in step 2③ is 24h; the TMA-V2CT in step 2④ x The mass fraction of the colloidal solution is 0.1%.

8. The method for preparing a TMA-MXene / CoV-LDH / NF composite material according to claim 1, characterized in that The molar ratio of cobalt chloride hexahydrate, vanadium chloride and urea described in step 3① is 15:12:10; the volume ratio of the amount of cobalt chloride hexahydrate described in step 3① to deionized water is 0.6mol:20mL; the TMA-V2CT described in step 3② x The volume ratio of the colloidal solution to solution I is 1:

2.

9. The method for preparing a TMA-MXene / CoV-LDH / NF composite material according to claim 1, characterized in that The temperature of the hydrothermal reaction described in step 3③ is 120°C, and the time of the hydrothermal reaction is 12h; the temperature of the vacuum drying described in step 3④ is 60°C to 80°C, and the time of the vacuum drying is 10h to 12h.

10. Use of a TMA-MXene / CoV-LDH / NF composite material prepared by the preparation method according to claim 1, characterized in that A TMA-MXene / CoV-LDH / NF composite material is used as a supercapacitor electrode material.

Citation Information

Patent Citations

  • Lamination structure NiCo2S4@NixCo(1-x)(OH)2 composite material preparation method and application

    CN108054019A

  • Preparation method and application of MOF-derived ZnS (at) CoS (at) NiV-LDH / NF composite material

    CN114597073A